Visitors’ fondness and satisfaction to urban recreational parks: the case of Bihere-Tsige Park, Addis Ababa, Ethiopia - Beshea Abdissa Chemeda; Dagne Getachew Woldemedhin; Demeku Mesfin; Fekede Terefe (Discover Global Society)
Abstract In crowded urban areas, open green spaces play a crucial role in leisure activities. People’s appreciation and enjoyment of recreational parks underscore the need to recognize the value of environmental services. This study investigates visitors' fondness and satisfaction with urban recreational parks, focusing on Bihere-Tsige Park in Addis Ababa, Ethiopia. A mixed-method approach was employed, including surveys and interviews to collect data from 120 respondents. The demographic and socioeconomic characteristics of respondents were analyzed, revealing that 96.7% of visitors were aged 16–35 years, with an average age of 26 years. The majority had completed secondary education (54.2%) or attained TVET education level (23.3%), with an average family size of two members. Travel costs averaged 13.7 ETB per round trip, and visitors spent an average of 3.6 h at the park per visit, with a monthly income average of 3545 ETB. The study found significant variation in visitor satisfaction with different park attributes. Specifically, 48.0% of visitors rated their satisfaction as medium, and 46.0% rated it as high. The study concludes that implementing effective resource conservation and enhancing amenities are crucial for improving visitor satisfaction. Recommendations include developing targeted marketing strategies and optimizing management of park resources to attract more visitors and ensure sustainable park use.